A catalogue of the types of Diapriinae (Hymenoptera, Diapriidae) at the Natural History Museum, London - Notton, David G. (European Journal of Taxonomy, 2014)
The types of nominal species of Diapriinae in the collection of the Natural History Museum, London, are catalogued. Lectotypes are designated for the following taxa: Diapria peraffinis Ashmead, 1896; D. smithii Ashmead, 1896; Galesus bipunctatus Ashmead,1894; G. (G.) foersteri var. nigricornis Kieffer, 1911; G. sexpunctatus Ashmead, 1893; G. walkeri Kieffer, 1907; Idiotypa nigriceps Kieffer, 1909; I. nigriceps Kieffer, 1911; I. pallida Ashmead, 1893; I. pallida Ashmead, 1894; Paramesius angustipennis Kieffer, 1911; P. cameroni Kieffer, 1911; Phaenopria cameroni Kieffer, 1911; P. halterata Kieffer, 1911; P. magniclavata Ashmead, 1896; Tropidopsis clavata Ashmead, 1893; T. clavata Ashmead, 1894. New combinations are proposed: Aneuropria bifurcata comb. nov. for Mantara bifurcata Dodd, 1920; Basalys quadridens comb. nov. for Microgalesus quadridens Kieffer, 1912; Coptera cratocerus comb. nov. for Galesus cratocerus Cameron, 1912; Coptera sexpunctata comb. nov. for Galesus sexpunctatus Ashmead, 1893; Doliopria magniclavata comb. nov. for Phaenopria magniclavata Ashmead, 1896; Spilomicrus aterrimus comb. nov. for Hoplopria aterrima Dodd, 1920; Spilomicrus campbellanus comb. nov. for Antarctopria campbellana Yoshimoto, 1964; Spilomicrus coelopae comb. nov. for Antarctopria coelopae Early, 1978; Spilomicrus diomedeae comb. nov. for Antarctopria diomedeae Early, 1978; Spilomicrus helosciomyzae comb. nov. for Malvina helosciomyzae Early & Horning, 1978; Spilomicrus insulae comb. nov. for Malvina insulae Early, 1980; Spilomicrus latigaster comb. nov. for Antarctopria latigaster Brues in Tillyard, 1920; Spilomicrus punctatus comb. nov. for Malvina punctata Cameron, 1889; Spilomicrus rekohua comb. nov. for Antarctopria rekohua Early, 1978; Trichopria bouceki comb. nov. for Oxypria bouceki Masner, 1959; Trichopria nigriceps comb. nov. for Tropidopria nigriceps Ashmead, 1894; Trichopria nigriceps comb. nov. for Xyalopria nigriceps Kieffer, 1907; Trichopria spinosiceps comb. nov. for Acidopria spinosiceps Dodd, 1920; Trichopria walkeri comb. nov. for Diapria walkeri Dalla Torre 1890. New replacement names are proposed: Coptera mosselensis nom. nov. for C. nigricornis Nixon, 1930 preocc.; Coptera pijiguaorum nom. nov. for C. sexpunctata Montilla & García, 2008 preocc.; Spilomicrus kozlovi nom. nov. for S. punctatus Kozlov, 1978 preocc.; Trichopria fluminis nom. nov. for T. nigriceps (Kieffer, 1907) preocc.; T. thermarum nom. nov. for T. nigriceps (Kieffer, 1913) preocc. New specific synonyms are proposed: Basalys cursitans (Kieffer, 1911) = B. pedisequa (Kieffer, 1911) syn. nov. (the former removed from synonymy with B. parvus Thomson, 1858); B. iphicla Nixon, 1980 = B. macroptera (Kieffer, 1911) syn. nov.; Coptera bipunctata (Ashmead, 1894) = C. sexpunctata (Ashmead, 1893) syn. nov.; Idiotypa nigriceps Kieffer, 1911 = I. nigriceps Kieffer, 1909 syn. nov.; I. pallida Ashmead, 1894 = I. pallida Ashmead, 1893 syn. nov.; Psilus nigricornis (Kieffer, 1911) = P. fuscipennis (Curtis, 1831) syn. nov.; P. walkeri (Kieffer, 1907) = P. fuscipennis (Curtis, 1831) syn. nov.; T. bouceki (Masner, 1959) = T. conotoma (Kieffer, 1911) syn. nov.; Trichopria halterata (Kieffer, 1911) = T. halterata (Kieffer, 1909) syn. nov. New generic synonyms are proposed: Antarctopria Brues in Tillyard, 1920 = Spilomicrus Westwood, 1832 syn. nov.; Malvina Cameron, 1889 = Spilomicrus Westwood, 1832 syn. nov.; Mantara Dodd, 1920 = Aneuropria Kieffer, 1905 syn. nov.; Microgalesus Kieffer, 1912 = Basalys Westwood, 1833 syn. nov.; Xyalopria Kieffer, 1907 = Trichopria Ashmead, 1893 syn. nov. (Xyalopria is removed from synonymy with Megaplastopria Ashmead, 1903). A brief account of some aspects of the history of these types is given.